Technological development and competition in the Ink Jet printers industry. - Liew, Kan Minh. (2008)
This dissertation reviews the key developments in the ink jet printer technology using different technology development theoretical frameworks. The review covers the history of ink jet development, R&D activities, marketing, manufacturing and company strategies. Using the different technology based frameworks, this paper is able to review the trends from various perspectives like development in material science, marketing strategies and organization change. This dissertation provides insights on how ink jet printing technology overtakes dot-matrix impact printing as the dominant technology in desktop printing and how HP is able to bring this technology to the mass market and remains as a market leader for more then 15 years.